O efeito das técnicas de extração na ação alelopática de diferentes órgãos da espécie exótica invasora Calotropis procera (Aiton) W. T. Aiton (Apocynaceae) - Santos, Riclecia Fraga (2023)
Plants produce different types and distinct amounts of secondary compounds during their life cycle, which can have allelopathic effects. According to the way in which these compounds are extracted, these positive or negative effects are changed, as the technique influences which compounds will be available in the solution, as well as their concentration. Thus, the aim of this study was to evaluate the effect of the extraction technique on the allelopathic action of different organs of Calotropis procera (Aiton) W.T. - Aiton (Apocynaceae), an invasive alien species For the production of the extracts, samples of roots, stems, leaves, flowers, green fruits and dried fruits were used, totaling six treatments. After drying, the samples were crushed and used for the preparation of the extracts through two techniques. In the aqueous crude extract (EBA), the samples were placed in distilled water in the ratio of 1:10 (dehydrated sample: volume of water) and kept at a temperature of 25 °C for 24 hours, with subsequent filtering. In turn, in the ultrasonic aqueous crude extract (EBAU), the samples were also placed in distilled water in the same proportion, but kept in ultrasound for 30 minutes, at 25 °C. The solutions produced by the two extraction techniques were tested at concentrations of 100, 90, 80, 70, 60, 50, 40, 30, 20, 10 and 0%, diluted in distilled water. The allelopathic action of these solutions was evaluated in the germination of lettuce seeds [Lactuca sativa L. (Asteraceae)], a model species for allelopathy studies. All organs presented allelopathic action negatively influencing germination, but the greatest allelopathic effect was observed in flowers and green fruits. The extracts produced from the ultrasound technique showed less allelopathic effect on the germinative parameters. The formation of seedlings was negatively affected by the extracts of the organs, but the EBAU technique promoted a greater allelopathic effect when compared to the EBA technique, especially for the extracts made from the reproductive structures of C. procera. It is concluded that extraction technique influences the allelopathic action of the different organs of C. procera and the reproductive organs of this species have greater alleloptic action.